Curriculum Analysis Of The Character Education System In Indonesia And Malaysia - Retno Anggraini; Ansori Ansori; Natal Kristiono; Rinovian Rais; Budi Mardikawati (PT. Banjarese Pacific Indonesia, 2025)
This research aims to analyze the comparison of character education system curricula in Indonesia and Malaysia, with a focus on the approach, implementation and effectiveness in shaping students' moral values ​​and character. The aim is to identify similarities and differences between the two education systems, as well as provide recommendations for improving the quality of character education in Indonesia. The research method used is a literature study with a qualitative approach. The research results show that Malaysia integrates character education through special subjects such as Islamic and Moral Education, while Indonesia emphasizes the integration of character values ​​in all subjects through the 2013 Curriculum. However, both countries face challenges in implementation, such as a lack of teacher training and gaps between theory and practice. The research results also reveal that Malaysia places more emphasis on religious values ​​and multiculturalism in character education, while Indonesia focuses on the values ​​of nationalism and diversity. Nevertheless, both countries agree that character education plays an important role in forming a generation with noble and responsible morals. Recommendations from this research are the need to increase teacher training, strengthen collaboration between schools, families and communities, as well as develop a more contextual and applicable curriculum. By adopting best practices from Malaysia and adapting them to the local context, Indonesia can increase the effectiveness of character education in forming students who are not only academically intelligent but also have strong character.